ATP Sensitive Potassium Channels in the Skeletal Muscle Function: Involvement of the KCNJ11(Kir6.2) Gene in the Determination of Mechanical Warner Bratzer Shear Force - Tricarico, Domenico; Selvaggi, Maria; Passantino, Giuseppe; De Palo, Pasquale; Dario, Cataldo; Centoducati, Pasquale; Tateo, Alessandra; Curci, Angela; Maqoud, Fatima; Mele, Antonietta; Camerino, Giulia M.; Liantonio, Antonella; et al. (Frontiers in Physiology, 2016)
The ATP-sensitive K+-channels (KATP) are distributed in the tissues coupling metabolism with K+ ions efflux. KATP subunits are encoded by KCNJ8 (Kir6.1), KCNJ11 (Kir6.2), ABCC8 (SUR1) and ABCC9 (SUR2) genes, alternative RNA splicing give rise to SUR variants that confer distinct physiological properties on the channel. An high expression/activity of the sarco-KATP channel is observed in various rat fast-twitch muscles, characterized by elevated muscle strength, while a low expression/activity is observed in the slow-twitch muscles characterized by reduced strength and frailty. Down-regulation of the KATP subunits of fast-twitch fibres is found in conditions characterized by weakness and frailty. KCNJ11 gene knockout mice have reduced glycogen, lean phenotype, lower body fat, and weakness. KATP channel is also a sensor of muscle atrophy. The KCNJ11 gene is located on BTA15, close to a QTL for meat tenderness, it has also a role in glycogen storage, a key mechanism of the postmortem transformation of muscle into meat. The role of KCNJ11 gene in muscle function may underlie an effect of KCNJ11 genotypes on meat tenderness, as recently reported. The fiber phenotype and genotype are important in livestock production science. Quantitative traits including meat production and quality are influenced both by environment and genes. Molecular markers can play an important role in the genetic improvement of animals through breeding strategies. Many factors influence the muscle Warner-Bratzler shear force including breed, age, feeding, the biochemical and functional parameters. The role of KCNJ11gene and related genes on muscle tenderness will be discussed in the present review.